Application Six Sigma Method in Green Leaf Threshing Tobacco Plant - Dian Wahyu Adriyanti; Iwan Vanany (IPTEK Journal of Proceedings Series, 2019)
Green Leaf Threshing (GLT) plant is an upstream company from the tobacco industries. The GLT main processing is separate the lamina from the stem and also dry out the tobacco into safe storage moisture content. One of the problems in the GLT factory is the high frequency of refeed / rework / reprocess on defective products. High refeed frequency increases production costs and eliminates customer trust. The aim of this study is to reduce refeed frequency. Six sigma is a methodology that can be used widely in manufacturing companies and services for continuous quality improvement. The Six sigma DMAI framework is used to find out the problems and solutions. The root cause of refeed are determined using fish bone diagrams and 5 Whys tool. The ranks for improvement are determined from the RPN using FMEA Analysis. The suggested program for improvement are investing tool, repairing tool and training worker. The results of identification indicate that defects due to inappropriateness moisture content are the highest cause of refeed. The results of the improvement indicate an increaseing sigma level from 3.72 to 3,97. The DPMO also declined from 13,220 to 6,823. Increasing sigma levelprovides benefit of Rp. 20.530.760.